Prospective study of management of long bone fracture by intra-medullary elastic nailing in children - Raut, Saijyot; Jain, Deepak; Gohil, Pratik; Malviya, Parimal; Vieira, Alfven; Agrawal, Tushar (International Journal of Research in Orthopaedics, 2020)
Background: The treatment of long bone fractures in children from 6 to 14 years is a challenging scenario. Titanium elastic nail (TEN) fixation was originally meant as a gold standard treatment method for femoral fractures, but was gradually applied to other long bone fractures in children, because it represents a middle path between conservative and surgical modality. Methods: In the present study paediatric patients in the age group of 6 to 14 year with long bone fractures to be treated with TEN in the Department of Orthopaedics were admitted to MGM Hospital (Kamothe) were selected. A total of 30 patients consenting to undergo this study were subjected for treatment after screening using the inclusion and exclusion criteria. Results: The mean age of the patients was 9.67±2.68 years. There was male preponderance (63.3%). In our study, RTA was observed to be the main cause of fracture (80%) whereas 20% fractures were due to fall. In our study, 50% patients had fracture of radius ulna followed by fracture of tibia 23.3%, femur (23.3%), and humerus (3.3%). The mean time to union was 5.30±1.06 weeks. Conclusions: TEN seems to be simple, biocompatible, more physiological, reliable and effective method of treatment of all long bone shaft fractures in 6 to 14 years old children. It is a rapid, safe and simple procedure with advantages of short operative time, minimal blood loss, shorter hospital stays early union, allowing early mobilization and early return to function with minimal complications.